Firm Fundamentals And Ipo Underpricing : Empirical Evidence From The Indonesian Stock Exchange - Meilin Veronica; Jhon Roni Coyanda (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2026)
IPO underpricing remains a persistent feature of emerging capital markets, raising questions about the effectiveness of firm-level signals in reducing information asymmetry during the IPO process. This study examines whether firm-specific characteristics and intermediary reputation significantly explain IPO discounting in the Indonesian Stock Exchange. Using a cross-sectional dataset of 123 firms that conducted Initial Public Offerings between 2021 and 2023, this study analyzes the association between IPO discount and firm profitability (Return on Assets), capital structure (Debt to Equity Ratio), firm age, underwriter reputation, and auditor reputation. Employing ordinary least squares regression with heteroskedasticity-robust standard errors, the empirical results reveal that none of the examined firm-level variables exhibit a statistically significant association with IPO discount. Rather than indicating empirical failure, these findings suggest that traditional signaling and certification mechanisms may have limited explanatory power in the Indonesian IPO market, where pricing outcomes appear to be more strongly influenced by market-wide factors, speculative demand, and investor sentiment. This study contributes to the IPO literature by providing evidence that challenges the universal applicability of conventional firm-level determinants of underpricing in an emerging market context. The findings carry important theoretical implications for information asymmetry and signaling theories, as well as practical implications for issuers and regulators by highlighting the need to incorporate market-level and behavioral factors in IPO pricing models. Future research is encouraged to adopt alternative empirical approaches and broader explanatory frameworks to better capture the heterogeneous nature of IPO pricing dynamics.